Students' Dictionary of Zoo and Aquarium Studies - Rees, Paul (CAB International, 2023)
A concise, affordable, illustrated dictionary for undergraduate and graduate students and pracitioners of zoo and aquarium studies and management
Description based on publisher supplied metadata and other sources